Innovation tools of economic development of the enterprise - Fedor Pavlovich Zotov; Rim Mugomovich Muzipov (Экономика региона, 2012)
Ways to generate new economic and financial benefits from the practice of rationalization work in the industrial enterprise are considered. An attempt to combine the practice rationalization work with the capabilities of tools and techniques of the modern management technologies is made. It is offered to learn the tools and techniques of the technologies by members of the 4types of the formed cross-functional teams through the tutorials. It is offered to distribute the tutorials between the four stages of the method PDCA management cycle. It is shown that the creation of teams and development of tutorials will create internal resources for innovation projects to achieve effective changes in economic development of the enterprise.